Keefektifan Model Pembelajaran Teams Games Tournament (TGT) Berbantuan Media Smartstep Pada Pembelajaran Mendalam Terhadap Keterampilan Menulis - Ramadani, Nur Laila; Sri Utaminingsih; Much Arsyad Fardani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low writing skills of students due to teacher-centered learning so that students tend to be passive. This study aims to analyze the effectiveness of the Teams Games Tournament (TGT) model on writing skills of procedural text writing skills in fourth grade students of SDN Mranak 2. The study used a quantitative method with a Pre-Experimental One-Group Pretest–Posttest design on 24 students, with data collection techniques through interviews, observations, and written tests. Data analysis used a paired sample T-Test to determine the average difference and the N-Gain Effectiveness Test to determine the interpretation of effectiveness with the help of SPSS 27. The results of the study showed a significance value of 0.001 <0.05 so that H_0 was rejected and H_a was accepted and the N-Gain value of 60.43% was included in the category of moderate effectiveness interpretation. Based on the results of the study, it can be concluded that there is effectiveness in the Teams Games Tournament (TGT) model assisted by smartstep media in in-depth learning on procedural text writing skills.